2016
DOI: 10.4137/cmamd.s38143
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Giant Cell Arteritis with Vertebral Artery Stenosis

Abstract: In giant cell arteritis (GCA), involvement of the vertebral arteries is rare with reported rates of 3%–4% for ischemic events secondary to vertebral artery stenosis or occlusion for those patients with GCA. This case study describes a patient who initially presented with acute onset of vertigo but was also found to have transient, side-alternating upper limb neurological findings. While initial imaging showed no vascular abnormalities, it was not until GCA was eventually confirmed with a temporal artery biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…Identifying VA involvement in GCA is important as it may result in ischemia in the vertebrobasilar territory, which is associated with high mortality ( 5 ). In our study, stroke at GCA diagnosis was detected in 12/57 patients (21.1%) by brain imaging, which is higher than published stroke rates of 2.4%–2.8% in the literature at the time of GCA diagnosis (between onset of GCA symptoms/signs and 1 month after beginning of GCs therapy) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying VA involvement in GCA is important as it may result in ischemia in the vertebrobasilar territory, which is associated with high mortality ( 5 ). In our study, stroke at GCA diagnosis was detected in 12/57 patients (21.1%) by brain imaging, which is higher than published stroke rates of 2.4%–2.8% in the literature at the time of GCA diagnosis (between onset of GCA symptoms/signs and 1 month after beginning of GCs therapy) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent case report of GCA with VA affection, progression of VA stenosis and recurrent stroke despite aggressive immunotherapy (high-dose GCs, cyclophosphamide, TCZ) was observed with a fatal outcome ( 7 ). Case reports with similar clinical course, i.e., recurrent vertebrobasilar ischemia in GCA with VA affection despite intensive immunotherapy with TCZ or cyclophosphamide, have been published ( 5 , 13 , 32 ). In patients with stroke due to progressive GCA who are non-responsive to immunotherapy or in patients with severe symptomatic stenosis based on an underlying inflammatory process, endovascular therapy (EVT) (e.g., angioplasty) may be considered ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome is usually poor, with a significant reduction of both survival and remission-free survival, despite high dosage of steroids [ 4 , 20 ] and immunosuppressants, such as cyclophosphamide (CFX) [ 21 ], methotrexate (MTX) [ 8 ], rituximab (RTX) [ 9 ] and, more recently, tocilizumab (TCZ) [ 9 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al [9] reported a case of GCA involving only the occipital artery which was revealed by magnetic resonance angiography. Chomlak et al [10] reported a case of GCA with vertebral artery involvement, which was refractory to immunosuppressives. Hocevar et al [11] claimed that, even early diagnosis and a prompt initiation of steroid did not prevent relapses in GCA.…”
Section: Discussionmentioning
confidence: 99%